A continuum model for lithium plating and dendrite formation in lithium-ion batteries: Formulation and validation against experiment. (April 2023) - Sahu, Smita; Foster, Jamie M.
Abstract: This work presents a novel physics-based model for lithium plating and dendrite formation in lithium-ion batteries. The formation of Li metal is an undesirable side-effect of fast charging and a primary contributor to cell degradation and failure. The model distinguishes between three types of plated Li metal, namely: (a) Li metal plated within the pores of the solid electrolyte interphase (assumed to be electronically connected to the anode and therefore recoverable); (b) dendrites protruding outside the SEI that remain electronically connected (and are therefore dangerous, potentially leading to a short circuit), and (c) electronically disconnected/"dead" Li metal outside the SEI contributing to capacity fade. The model is validated against two independent experiments. First, measurements of: (i) the cell voltage and current during a constant-current–constant-voltage charge and subsequent discharge, and (ii) the Li metal intensities (derived from operando NMR) which directly quantifies the time-resolved quantity of Li metal in the cell during use. Second, against voltage measurements during galvanostatic discharge at a range of C-rates and temperatures. Favourable agreement is demonstrated throughout; particularly in terms of the proportions of reversible and irreversible plating. We also demonstrate that the model reproduces the well-documented trends of being more prevalent at increased C-rate and/or decreased temperature. Highlights: Novel continuum model for lithium plating and dendrite formation presented. Discerns irreversible vs. reversible plating. Discerns dangerous live dendrites vs. dead/inert Li. Cogent explanation for dead lithium formation is offered. Comparison with state-of-the-art experimental data, excellent agreement demonstrated.